2006
DOI: 10.1016/j.jacc.2005.12.076
|View full text |Cite
|
Sign up to set email alerts
|

Protected Carotid Stenting in High-Risk Patients With Severe Carotid Artery Stenosis

Abstract: For some patients with severe carotid stenosis and high-risk features for carotid endarterectomy, carotid artery stenting with distal embolic protection is a reasonable alternative for revascularization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
1
3

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 182 publications
(113 citation statements)
references
References 11 publications
3
106
1
3
Order By: Relevance
“…[245][246][247][248][249][250][251] If properly deployed, an EPD can reduce the neurological risks associated with CAS, but these devices may also be associated with failures. 53,196,198,247,[252][253][254][255][256][257][258] Among the general risks is access-site injury, which complicates 5% of cases, but most such injuries involve pain and hematoma formation and are self-limited. [259][260][261][262] Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%
“…[245][246][247][248][249][250][251] If properly deployed, an EPD can reduce the neurological risks associated with CAS, but these devices may also be associated with failures. 53,196,198,247,[252][253][254][255][256][257][258] Among the general risks is access-site injury, which complicates 5% of cases, but most such injuries involve pain and hematoma formation and are self-limited. [259][260][261][262] Contrast-induced nephropathy has been reported in <1% of cases, because CAS is generally avoided in patients with severe renal dysfunction.…”
Section: Carotid Artery Stentingmentioning
confidence: 99%
“…1,2 In the past few years, however, carotid angioplasty and stent placement (CAS) has emerged as an alternative endovascular treatment strategy for these disorders. Although initial single-center case series and registries have reported acceptable periprocedural complication rates after CAS even in surgical high-risk patients, [3][4][5][6] recent randomized trials directly comparing CAS with CEA have produced conflicting results. [7][8][9] Compared with surgery, CAS potentially has the major disadvantage of producing more emboli to the brain, 10 which has led to the development and widespread application of cerebral protection devices aimed at preventing the passage of embolic material into the cerebral vasculature.…”
mentioning
confidence: 99%
“…Strict control of hypertension is one of the preventive measures that has received the most attention. Most Investigators recommend strict control of BP in the postoperative period to prevent ICH after CEA (Ahn et al, 1989;Bernstein et al, 1984;Bove et al, 1979;Buhk et al, 2006;Hosoda et al, 2001;Ko et al, 2005;Roh et al, 2005;Safian et al, 2006;Tang et al, 2008) and after CAS, as we will see below. It has been suggested that even BP in the normal range may be deleterious in patients at high risk for CHS (Piepgras et al, 1988;Ouriel et al, 1999;Jorgensen & Schroeder, 1993).…”
Section: Prevention and Treatmentmentioning
confidence: 97%